THE ROLE OF NEOLOGISMS IN BRITISH NEWSPAPERS - Azimova Sevara Jamshid Qizi; Seytimbetova Aykumar Pulatbaeva (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation. The theoretical underpinnings and historical evolution of neologisms in the English language are examined in this article. It illustrates the primary language theories—structural, etymological, stylistic, and lexicographic—that are used to investigate neologisms. The study looks at the technological and sociocultural elements that influence the creation of new lexical units and assesses how they contribute to the ever-changing English vocabulary. The procedures by which words are formed and the standards by which neologisms are incorporated into common usage are given special consideration. According to the article’s conclusion, neologisms are a crucial component of linguistic evolution and a reflection of social change.